Exchange Characteristics of Lead, Zinc, and Cadmium in Selected Tropical Soils - Tope O. Bolanle-Ojo; Abiodun D. Joshua; Opeyemi A. Agbo-Adediran; Ademola S. Ogundana; Kayode A. Aiyeyika; Adebisi P. Ojo; Olubunmi O. Ayodele (International Journal of Agronomy)
Conducting binary-exchange experiments is a common way to identify cationic preferences of exchangeable phases in soil. Cation exchange reactions and thermodynamic studies of Pb2+/Ca2+, Cd2+/Ca2+, and Zn2+/Ca2+ were carried out on three surface (0–30 cm) soil samples from Adamawa and Niger States in Nigeria using the batch method. The physicochemical properties studies of the soils showed that the soils have neutral pH values, low organic matter contents, low exchangeable bases, and low effective cation exchange capacity (mean: 3.27 cmolc kg−1) but relatively high base saturations (≫50%) with an average of 75.9%. The amount of cations sorbed in all cases did not exceed the soils cation exchange capacity (CEC) values, except for Pb sorption in the entisol-AD2 and alfisol-AD3, where the CEC were exceeded at high Pb loading. Calculated selectivity coefficients were greater than unity across a wide range of exchanger phase composition, indicating a preference for these cations over Ca2+. The Keq values obtained in this work were all positive, indicating that the exchange reactions were favoured and equally feasible. These values indicated that the Ca/soil systems were readily converted to the cation/soil system. The thermodynamic parameters calculated for the exchange of these cations were generally low, but values suggest spontaneous reactions.